Aminophosphonic Acids and Derivatives. Synthesis and Biological Applications - Orsini, F.; Sello, G.; Sisti, M. (Current Medicinal Chemistry, 2010)
In recent years, phosphonic acids and their derivatives have received increasing attention as analogues of a series of naturally occurring phosphates and as “bio-isosteric phosphorus analogues” of aminoacids. Unlike a phosphate group, the phosphonate moiety is not readily hydrolyzed, in a biological environment, by the enzymes involved in the phosphate cleavage. This feature makes these compounds extremely useful in several applications, in metabolic regulation, in enhancement or inhibition studies, in the development of potential drugs against several metabolic disorders. The great potential of these compounds in biological applications resulted in an intense effort directed to the development of efficient synthetic methods for their preparation, with particular attention to stereoselective synthesis. The purpose of this review is to give an up-to-date account of the chemistry, the synthesis and the biological activity of aminophosphonic acids and their derivatives.
Keywords: Aminophosphonates